Technology, Taphonomy, and Seasonality: Understanding Differences between Dorset and Thule Subsistence Strategies at Iqaluktuuq, Victoria Island - Howse, Lesley; Friesen, T. Max (ARCTIC, 2017)
This paper examines differences between Late Dorset and Thule Inuit subsistence economies at the Bell site on Victoria Island, Nunavut. This location is relatively unusual in the eastern Arctic region because local subsistence was based largely on caribou and fish, rather than the sea mammals that dominate in most other regions. For both periods, animal bone samples are quantified in terms of taxonomic frequencies, element (body part) distributions, seasonality, prey demography, and bone modifications such as cutting, burning, and gnawing. A comparison between the periods indicates many broad similarities in subsistence, but some subtle differences suggest that the Thule had a more focal and specialized economy, with a slightly different seasonal profile. Le présent article porte sur les différences entre l’économie de subsistance du Dorsétien récent et l’économie de subsistance des Inuits thuléens au site Bell de l’île Victoria, au Nunavut. Cet emplacement de la région est de l’Arctique est assez inhabituel en ce sens que la subsistance de la région reposait grandement sur le caribou et le poisson, et non pas sur les mammifères marins qui dominent la plupart des autres régions. Pour ces deux périodes, les échantillons d’ossements d’animaux sont quantifiés en fonction des fréquences taxonomiques, de la répartition des éléments (restes), de leur saisonnalité, de la démographie des proies et des altérations subies par les os, comme les marques de coupure, de brûlure et de rongement. La comparaison des périodes permet de remarquer de nombreuses similitudes générales sur le plan de la subsistance, mais certaines différences subtiles suggèrent que les Thuléens avaient une économie plus concentrée et spécialisée de même qu’un profil saisonnier légèrement différent.